'Maisha yetu ya kila siku kama vile movie': Fantasy, desire and urban space in Tanzanian music videos. (1st December 2019) - Kerr, David
AbstractAn explosion of creative practices in music, film and video production followed the liberalization of the Tanzanian media in the early 1990s. Concerned about cultural imperialism, Tanzania's first president Julius Nyerere had resisted allowing television in mainland Tanzania and consequently the first licence was only granted in 1994. Following the establishment of the first TV station there has been a proliferation of TV station and online platforms circulating the new genre of popular music videos. During the last decade, new media spaces, including continent-wide TV channels such as Channel O and MTV Africa (both based in South Africa), have created new circuits for the circulation of Tanzanian music videos. New media spaces enabled by liberalization have become sites for negotiating gendered, moral and sociopolitical value. They also serve as imaginative sites of desire and fantasy. Music videos set in the cinematic space of Dar es Salaam's new high-rise buildings and 'exclusive' clubs have become something of a trope in Tanzania. These videos display fantasies of enjoyment and consumption. In so doing, they reflect neo-liberal and individual modes of wealth accumulation which challenge accepted social norms about consumption and wealth. Examining these new contemporary cinematic representations of the city as spaces of fantasy and desire, this article will explore the modes of spectatorship audiences bring to these videos. It will examine how audiences, largely excluded from these exclusive city spaces of consumption and excess, read cityscapes in music videos. This article ultimately sets out the multiplicity, ambiguity and indeterminacy of the desires (both creative and destructive) evoked in audiences by contemporary music video.